Apolipoprotein E genotype and in vivo amyloid burden in middle-aged Hispanics. (13th October 2020) - Palta, Priya; Rippon, Brady; Reitz, Christiane; He, Hengda; Sherwood, Greysi; Ceballos, Fernando; Teresi, Jeanne; Razlighi, Qolamreza; Moreno, Herman; Brickman, Adam M.; Luchsinger, José A.
Abstract : Objective: To examine in vivo amyloid burden in relation to APOE ε4 genotype in middle-aged Hispanics. We hypothesize higher amyloid levels among APOE ε4 carriers vs APOE ε4 noncarriers. Methods: This is a cross-sectional study in a community-based sample of 249 middle-aged Hispanics in New York City who underwent a 3T brain MRI and PET with the amyloid radioligand 18 F-florbetaben. APOE genotype was the primary exposure. The primary outcome was amyloid positivity. The secondary outcome was subthreshold amyloid levels examined as a continuous variable. Results: APOE ε4 carriers (n = 85) had a higher frequency (15.3%) of amyloid positivity compared to APOE ε4 noncarriers (n = 164, 1.8%). In the subthreshold group of amyloid-negative participants (n = 233), APOE ε4 carriers (n = 72) had a 0.02 (95% confidence interval [CI] 0.01–0.04) higher global brain amyloid standardized uptake value ratio (SUVR) compared to APOE ε4 noncarriers (n = 161). Compared to participants with the ε3/ε3 genotype, participants with ε4/ε4 had the highest frequency of amyloid positivity (28.6%), followed by those with ε3/ε4 (11%). Among amyloid-negative participants (n = 233), compared to participants with ε3/ε3 (n = 134), those with ε4/ε4 (n = 5) had a 0.12 (95% CI 0.07–0.17) higher global brain amyloid SUVR, and those with ε3/ε4 had a 0.02 higher SUVR (95% CI 0.003–0.04). Results were similar when a median split was used for elevated amyloid, when continuous amyloid SUVR was analyzed in all participants, and in nonparametric Mann-Whitney comparisons. Conclusion: Middle-aged Hispanic APOE ε4 carriers have higher in vivo brain amyloid burden compared with noncarriers, as reported in non-Hispanics.